Assessment of Corporate Safety Across Economic Sectors During The Second Wave of SARS COV2 Crisis - The Employees’ Perspective - Wojciech PIESTRZYNSKI; Ewa MATUSKA (Communications of International Proceedings, 2020)
The paper presents the analysis of quantitative research conducted during second wave of the economic crisis caused by Covid-19 pandemic among the sample (N=795) of Polish employees representing three economic sectors: services, production and public sector. Two variables: the type of the sector and the level of the subjective sense of safety and their elements were statistically controlled via two-way analysis followed. Obtained results show employees differ in their experiencing prolonged stress caused by the COVID-19 pandemic and most of them (employed in service and in production sector) perceive disturbances in their subjective sense of safety. Employees of all economic sectors connect their sense of safety with the degree of satisfaction of their basic needs, the safety of their relatives, and their appreciation of the corporate order currently existing in their organizations. The employees’ assessment of the corporate safety is more critical in case of enterprises, both in service and in production, in compare to the evaluation of public sector organizations. The found results can be used as recommendations for introducing more intense and accurate anti-crises interventions addressed to the sector of enterprises.
Keywords: corporate safety; sense of safety; employees; COVID-19 crisis